TIKTOK APPLICATION AS A PROJECT-BASED ARABIC LEARNING MEDIA - Hesty Maulida Eka Putry; Muassomah, Muassomah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
TikTok has once been seen bad by the public and even banned by the Indonesian government. The advantage of TikTok applications, one of which is a medium of Project-Based Learning, is, thus, a challenge to gain. This paper aims to describe the use of the TikTok application as a medium for Arabic language learning through Project-Based Learning on vocabulary material carried out at Madrasah Aliyah Nahdlatul Wathan (MA NW) Pringgasela and to reveal students' perspectives regarding this matter. This paper is packaged with a qualitative descriptive approach, while data collection is through observation and interviews. The data analysis technique uses the Miles and Huberman model, i.e. reducing data, presenting data, and drawing conclusions. This study concludes that using the TikTok application as a learning medium can be an innovation in Arabic learning. The strengths felt by students include: learning becomes more exciting and less boring, students get new experiences, students become more active, and it is easy to memorize the vocabulary they learn. The study also finds that the drawbacks of this application are that it takes a long time in the manufacturing process, requires an internet connection, and the lack of teacher supervision in using the TikTok application outside of school.